Attitudes toward the theory of evolution and its misconceptions in Tromsø, Northern Norway - Joel Vikberg Wernström; Vanessa Molin Paynter; Ossian Hagevi; Andreas Altenburger (Evolution: Education and Outreach)
Abstract Background Evolution is the core of modern biology, but various misconceptions are persistent companions to the theory. The intuitively appealing but discredited suggestion that organisms innately tend to evolve in a predefined direction still lingers, and remains commonly referenced by biologists, the popular media and even educators in the form of so-called ‘evolutionary shorthand’. The flawed logic of goal-oriented evolutionary hypotheses such as orthogenesis and teleology is known to negatively impact students’ ability to understand evolution, but may remain widespread among the public even in countries where evolution acceptance is high. We have distributed a questionnaire to explore the attitude of respondents in Tromsø, a town in northern Norway, towards accurate evolutionary statements while also asking whether they agree with common misconceptions related to goal-orientation in evolution and hierarchies in nature. Results Most of the 307 respondents considered evolution to be the best explanation for the origin of species and the development of life on Earth and agreed also to other accurate statements of current evolutionary theory. Nevertheless, a substantial proportion of respondents agreed to common misconception statements which e.g. synonymised evolution with improvement, reflected the great chain of being, and described evolution as a progressive process that tends to result in higher complexity and intelligence. Respondents’ inclination towards such evolutionary misconceptions differed significantly based on education level and occupation, and our correlation matrix visualisation indicates that higher agreement with accurate evolutionary statements is associated with lower agreement with misconceptions. Respondents with a university education or an occupational affiliation with biology, and people between 31 and 50 years of age held the lowest degrees of misconceptions. Conclusions Our results provide a snapshot of current attitudes to evolution and common misconceptions of the theory of biological evolution in Tromsø. While evolution is widely accepted, a substantial proportion of respondents agree to describe the process as goal-oriented and hierarchical in line with discredited evolutionary concepts such as orthogenesis. Based on our observation of an acceptance-understanding discrepancy and the fact that evolutionary misconceptions are not uncommon among the public in Tromsø, we welcome a wider debate among biology educators in Norway on how to best teach the theory.